Synthesis and Characterisation of the First Oxazoline Coordination Compounds Containing the Cu(F6acac)2 Unit: X-ray Diffraction Studies of Cu(kappa2-O,O'-F6acac)2(kappa1-N-Meox) and Cu(kappa2-O,O'-F6acac)2(kappa1-N-Etox) - Yadav, Paras N.; Barclay, Tosha M.; Gossage, Robert A. (Journal of Nepal Chemical Society, 2013)
The synthesis and characterisation (elemental analysis, IR, X-ray diffraction) of the first two oxazoline coordination compounds of Cu(F6acac)2 are described. Both of these complexes are five-coordinate mononuclear formally Cu(II) materials with a slightly distorted square pyramidal coordination motif around the metal centre. The structures are compared and contrasted to other N-donor complexes of Cu(F6acac)2. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8059 Journal of Nepal Chemical Society Vol.28, 2011 Page: 54-58 Uploaded date: May 7, 2013